A system for localising and searching objects to enhance self-directed practical learning. (11th November 2010) - Jing, Lei; Cheng, Zixue; Huang, Tongjun
We are living in an era of knowledge explosion. The meaning of knowing has shifted from being able to remember and repeat information to being able to find and use it (Simon, 2000). Practical learning has been proved as an effective way to arouse learner's curiosity and deepen the understanding on a given subject. To perform practical learning more effectively, supervisors are necessary to recommend proper learning material and give instructions in the learning process. Up to now, however, human beings are the only candidate to act as supervisors in the learning process which has hindered the learner's practical learning activity. In this paper, we propose a computing system which can substitute human beings to act as supervisors to recommend proper experimental learning contents to the learner and help the learner to accomplish the experiment process.